2021
DOI: 10.1186/s13195-021-00896-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational programme on Alzheimer’s disease patients’ quality of life: results of the randomized controlled trial THERAD

Abstract: Background Although educational interventions are recommended in Alzheimer’s disease (AD), studies assessing the impact of interventions such as “therapeutic patient education” are scarce. Indeed, the intrinsic nature of the disease is considered a barrier to patients’ involvement in such approaches. We aimed to evaluate an intervention by using a “dyadic” approach (patient and caregiver) in both intervention and assessment. Methods THERAD is a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…This result is in the same line as, Villars, et al, (2021), who concluded that age, marital status, educational level,and occupational status are highly associated and related tothe total quality of life of the caregivers of Alzheimer's patients. Furthermore, the findings were confusing in that there was a statistically highly significant difference in the stress evaluation between caring relatives' work status and annual income in the preprogram period.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This result is in the same line as, Villars, et al, (2021), who concluded that age, marital status, educational level,and occupational status are highly associated and related tothe total quality of life of the caregivers of Alzheimer's patients. Furthermore, the findings were confusing in that there was a statistically highly significant difference in the stress evaluation between caring relatives' work status and annual income in the preprogram period.…”
Section: Discussionsupporting
confidence: 86%
“…Burden and Quality of Life in Patients Diagnosed with Alzheimer's Disease", concluded that education in the program reduced the burden of care for caregivers of Alzheimer's patients and had a positive impact on their quality of life.This finding contradicts Villars, et al, (2021), who highlight the impact of educational programs on Alzheimer's patients' quality of life, although the results of randomized controlled studies do not support this claim. After two months, therapeutic patient education had a substantial effect on nurse-reported patient QOL, but not on self-reported patient QOL.…”
Section: Discussionmentioning
confidence: 67%
“…Results of the concurrent study showed that there was a highly statistically significant difference between the age of the caregivers and their quality of life. From the researcher's point of view, these findings donate the effectiveness of personal characteristics of the caregivers particularly age which is the basics of life and affect strongly on their quality of life.This result came in the same line with, Villars, et al (2021), who concluded that age, marital status, educational level, and occupational status are highly associated and related tothe total quality of life of the caregivers of Alzheimer's patients.…”
Section: Discussionsupporting
confidence: 86%
“…The study protocol has been detailed elsewhere, 9 and the results recently published. 10 The participants were 196 community-dwelling people with mild to moderately severe AD 11 and their caregivers (196 dyads, 98 in each group) recruited in the geriatric department of the Toulouse Hospital between 2013 and 2015. The intervention was composed of individual sessions (for patients and caregivers) and group sessions (caregivers only).…”
Section: Methodsmentioning
confidence: 99%